W and Z production in association with light and heavy-flavour jets at the LHC and the Tevatron - Dunford, Monica (The European physical journal. Web of Conferences, 2013)
Measurements of W and Z production in association with jets provide a stringent test of perturbative QCD calculations. In addition, these measurements are of great relevance to searches for new particles and new interactions as these Standard-Model processes often represent a significant background. In these proceedings, recent results on the W and Z production for light and heavy-flavour jets at the Tevatron and the LHC are presented.
Gesehen am 05.01.2021